A FINDING LIST OF HIGH LUMINOSITY STARS AROUND CYGNUS AND CEPHEUS - GONZALEZ, G; GONZALEZ, G (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1952)
A list is given of 71 stars classified on objective prism plates a belonging to the group "OB". The stars included in the present list were found on plates taken by means of the 26-30 inch Tonantzintla Schmidt camera and a 4 degrees objective prism.
BOL OBS TONAN TACUB
Keywords: FINDING LIST, HIGH LUMINOSITY, STARS, AROUND, CYGNUS, CEPHEUS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS